Makna Dan Fungsi Label Kehormatan Israel Dalam Keluaran 19:6 Ditinjau Dari Teori Identitas Sosial - Serepina Hasibuan (Jurnal Apokalupsis, 2021)
The Israel's honorific label was given by the LORD God to the Israelites who had just come out of Egypt at Mount Sinai. Explaining the identity label, then understanding the Israel’s honor label certainly aims to form the social and spiritual identity of the Israelites. This article will discuss the meaning and function of honor labels through interdisciplinary studies between biblical studies using textual criticism and social psychology sciences, namely SIT. By using these two disciplines, the writer gets a fresher and brighter interpretation, especially regarding the meaning and function of Israel's honorific label in Exodus 19:6. From the research that has been done, the meaning of the honorific labels “מַמְלֶ֥כֶת כֹּהֲנִ֖ים” (mamlekhet kohanim) and “ג֣וֹי קָד֑וֹשׁ” (goy qadosh) is to express the identity of a nation of slaves who have been elevated to a kingdom of priests and a holy nation by GOD who has made a covenant with their forefather Abraham. Meanwhile, the function of giving the honorary label in Social Identity Theory/SIT's point of view is to raise the nation's self-esteem, express the appreciation contained in faith and encourage the nation to behave in accordance with their social and spiritual identity as the "Kingdom of Priests" and "Holy Nation"